RAPID DISTRIBUTION OF THE CHINESE LANGUAGE AND CULTURE IN KAZAKHSTAN WITHIN THE FRAMEWORK OF "ONE BELT - ONE ROAD" - Sharipkazy, N.; Kerimbayev, E. (Journal of Oriental Studies, 2022)
One of the features of international relations in the 21st century is the use by developed countries of the concept of "soft power" in the implementation of a long-term international strategy. A striking example is the rapidly developing state of China in recent years. The concept of "soft power" implies the desire of the Chinese government to spread its national language and culture around the world. The main reason why countries easily and quickly accept this policy is the growth of China’s economic influence in the world, as well as the development and mutual interest of trade and economic ties with countries around the world. Therefore, the interest of the countries of the world to China has increased, the desire to study its language and historical culture has increased. China began to pursue a policy of generalizing the Chinese language and culture to the world by creating institutions named after Confucius, the great humanist thinker. Thus, the teaching of Chinese has become an important content of China’s foreign policy. Language policy and language planning have always been an effective tool in solving a number of issues of domestic and foreign policy, and in the context of today’s globalization, its importance has increased. In recent years, the urgency of the problem of foreign language policy is growing day by day, and the place of individual actions taken by states in this direction is occupied by a purposefully planned foreign language policy. Consideration of the purpose, subjects and means, mechanisms of language policy, as well as its relationship with the concept of "soft power", which has become increasingly widely used, is becoming an interesting and important object of study today. In modern geopolitical conditions, China’s policy in this area attracts the attention of the whole world. The article emphasizes that the PRC’s "One Belt One Road" project is a new model for globalization, it intends to make efforts both in the economy and in the humanitarian sphere. Since the introduction of this project, China has been actively promoting the Chinese language and Chinese culture in our country.